Sustainable Business Development System Increasing Omzet Through Technopreneurship In Small To Medium Industries (SMIs) - Suranto Suranto; Wildan Asyraf Azinuddin; Ahmad Kholid Alghofari; Afiqoh Akhmalia Fahmi (SEAN Institute, 2023)
This research aims to determine the condition of the business and determine the priority of alternative strategies that are appropriate for SMIs. This research a quantitative methodology, the object of the research was carried out at Masaran batik SMIs with the stages of research through the analysis of internal and external factors SWOT analysis, strategic planning through strategic planning and prioritization of alternative strategies and criteria using the multi attribute model. Research will be conducted on business development strategies with strength, weakness, opportunities, threats (SWOT) analysis, Quantitative Strategic Planning Matrix (QSPM) and Multi Attribute Utility Theory (MAUT). The results of the research, the priority of the top alternative strategies for SMIs is to conduct online sales, increase online marketing strategies and cooperate with batik marketing souvenir centers. This study discusses the implementation of technopreneurship in marketing to build entrepreneurial success.